Analisis Perkembangan Epistemologi Hukum di Indonesia dalam Upaya Membangun Konvergensi Epistemologi Hukum - Yogi Prasetyo; Imam Zaelani; Rangga Sakti (University of Merdeka Malang, 2019)
This article is research result that describes development of the epistemology of law in indonesia, relationship of epistemology in law, and the concept of convergence of epistemology in law. The research method used is a literature study with a philosophical approach. The research results draw; epistemology of law based on empirical reality by inductive approach like sociology of law; epistemology of law based on rational sense by deductive approach like positivistic normative law; epistemology of law based on moral-ethics and conscience by using awareness and intuitional approach; epistemology of law based on Al-Quran like God’s law. These results show a correlation independent, parallel and linier in the epistemology of law. This correlation claims the certain truth and causes law is used for certain purposes. Based on this reason, it needs convergence of epistemology in law that unites the law truth, so that law can be comprehended by various perspectives.How to cite item: Prasetyo, Y., Zaelani, I., Sakti, R. (2019). Analisis Perkembangan Epistemologi Hukum di Indonesia dalam Upaya Membangun Konvergensi Epistemologi Hukum. Jurnal Cakrawala Hukum, 10(1), 96-106. doi:https://doi.org/10.26905/idjch.v10i1.2501